Liquidity Risks of Crypto Asset Investments - Batara David Martin Siregar; Herry Subagyo; Dwi Eko Waluyo (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2024)
This study examines the liquidity risk of cryptocurrency investments and the factors influencing it. The data used includes the cryptocurrency market, encompassing more than 400 exchanges, and over 13,000 types of cryptocurrencies in Indonesia. The method employed is descriptive analysis with a normative approach, utilizing secondary data collection as well as direct and indirect interviews with sources from Aspakrindo (Indonesian Crypto Asset Traders Association), official Bappebti-registered exchanges such as PINTU and Tokocrypto, as well as cryptocurrency trader and investor communities in Indonesia. The findings indicate that liquidity risk is significantly influenced by trading volume and the supporting community of a particular market or cryptocurrency asset.